(untitled) (Theatrum historiae, 2009)
The aim of the paper is to present an introduction into a topic concerning the ways men and women lived and worked together within the space of a medieval Czech or, more precisely, Moravian town. The text neither draws on any previous research nor does it develop any prior findings as there are no relevant findings to this topic available up to the present day. It rather outlines some basic questions and theses. It also reflects on specific methods of gender-oriented research of medieval resources and difficulties that a mediaevist may face when dealing with this issue.